From Game to Gain: Utilizing Mobile Legends New Terminologies to Enrich EFL University Students' Vocabulary and Comprehension - Ma'ruf, Habib Toha; Andayani, Endah Alamsari; Aisyah, Siti; Putranto, Henry Rio; Prasetyo, Yudy (Journal of English Language and Education, 2025)
Mobile gaming, as a rapidly expanding industry, has introduced unique linguistic elements into daily communication, particularly among university students. While these terms may support EFL learners in improving their language skills, research in this area remains limited. This study aims to explore the newly emerging terms in Mobile Legends and their potential impact on EFL university students’ vocabulary growth and reading comprehension. A total of 35 students participated in gameplay-based learning sessions, and data were gathered using vocabulary tests, comprehension tasks, and reflective journals through a mixed-method approach. The findings suggest that consistent exposure to gaming terms from Mobile Legends significantly broadens students’ vocabulary and enhances their understanding of reading materials. Additionally, students reported higher motivation and engagement when learning English through gaming. The study concludes that incorporating gaming language as supplementary material in the EFL classroom can play a valuable role in supporting vocabulary acquisition and improving comprehension outcomes.